Dean List Award Ceremony and Academic Advisor Day 2023 - Noraziah, Adzhar (Pusat Sains Matematik UMPSA, 2023)
The Dean List Award Ceremony & Academic Advisor Day was held on Saturday, 17th June 2023 from 8.00 AM to 1.00 PM.